Pengaruh Penggunaan Media Roda Putar terhadap Hasil Belajar IPA Siswa Kelas V SDN Banyubiru 01 - Gusman, Yessy Rossyana; Widayati, Sri; Wijayanti, Atrianing Yessi (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2023)
The background to this research is that the low science learning outcomes of class V students at SDN Banyubiru 01 are due to the teacher still using the lecture method so that students only compete with the teacher and students feel bored in the learning process. By using a rotary wheel media, students will have a high curiosity in the learning process. This study uses quantitative research. The data collection technique used is in the form of a test. The results of the study show that there is an effect of the use of rotary wheel media on science learning outcomes. This can be proven by the acquisition of hypotensive test results with the t test formula, namely with the calculated t value greater than t table (5.10504> 2.042) then Ha is accepted and Ho is rejected.Keywords: rotating wheel media, science learning outcomes.